The Federal Democratic Republic of Ethiopia : Debt Sustainability Analysis. (IMF Staff Country Reports; Country Report ;, 2005)
This paper presents key findings of debt sustainability analysis (DSA) for Ethiopia. The stress tests reveal that Ethiopia's external debt and debt service indicators are particularly sensitive to the terms of new borrowing and negative export shocks. The baseline projections appear fragile to adverse shocks and embody optimistic assumptions relative to Ethiopia's historical trend over the past 10 years. The public debt DSA indicates some risk arising from output growth and the primary balance remaining at historical averages.